Isoalantolactone Enhances the Antitumor Activity of Doxorubicin by Inducing Reactive Oxygen Species and DNA Damage - Wu, Fengjiao; Shao, Rongrong; Zheng, Peisen; Zhang, Tingting; Qiu, Chenyu; Sui, Hehuan; Li, Shaotang; Jin, Libo; Pan, Huanle; Jin, Xiance; Zou, Peng; Cui, Ri; et al. (Frontiers in Oncology, 2022)
Colon cancer is one of the most common cancer in the world. Doxorubicin (DOX) is a classical anti-tumor drug which widely used in treatment of cancers, however, high toxicity limited its further clinical application. Thus, it is urgent to find new drugs with low toxicity and high efficiency to treat colon cancer. Isoalantolactone (IATL), an isomeric sesquiterpene lactone isolated from the plant of inula helenium, has been reported to have anti-cancer activity against a variety of cancer cells. However, the function of IATL in colon cancer remains unclear. Here, we demonstrated that IATL inhibited colon cancer cell growth by increasing cellular reactive oxygen species (ROS) production. Further study showed that ROS accumulation contributed to DNA damage and JNK signaling pathway activation. In addition, we found that IATL markedly enhanced DOX-induced cell cytotoxicity in colon cancer cells. IATL in combination with DOX significantly increased the ROS production, induced DNA damage and activated JNK signaling pathway. Taken together, our data suggested that combined treatment with IATL and DOX may serve as a potential therapeutics for colon cancer.